Intracerebral hemorrhage research from bench to bedside - Zhang, Jian-xiang; Colohan, Austin (Acta neurochirurgica supplements, 2011)
The volume includes 75 papers which were presented at the Third International Conference on Intracerebral Hemorrhage, held in Rancho Mirage, California, in March 2010. The topics treated include animal models, pathophysiology of cerebral hemorrhage, experimental treatment for cerebral hemorrhage, cerebral hemorrhage clinical manifestations, prognosis of cerebral hemorrhage, and clinical management. The articles represent the recent advances in hemorrhagic brain injury research presented by highly respected laboratories around the world.